The Functions of Hepatitis B Virus Encoding Proteins: Viral Persistence and Liver Pathogenesis - Zhao, Fenglin; Xie, Xiaoyu; Tan, Xu; Yu, Hongli; Tian, Miaomiao; Lv, Huanran; Qin, Chengyong; Qi, Jianni; Zhu, Qiang (Frontiers in Immunology, 2021)
About 250 million people worldwide are chronically infected with Hepatitis B virus (HBV), contributing to a large burden on public health. Despite the existence of vaccines and antiviral drugs to prevent infection and suppress viral replication respectively, chronic hepatitis B (CHB) cure remains a remote treatment goal. The viral persistence caused by HBV is account for the chronic infection which increases the risk for developing liver cirrhosis and hepatocellular carcinoma (HCC). HBV virion utilizes various strategies to escape surveillance of host immune system therefore enhancing its replication, while the precise mechanisms involved remain elusive. Accumulating evidence suggests that the proteins encoded by HBV (hepatitis B surface antigen, hepatitis B core antigen, hepatitis B envelope antigen, HBx and polymerase) play an important role in viral persistence and liver pathogenesis. This review summarizes the major findings in functions of HBV encoding proteins, illustrating how these proteins affect hepatocytes and the immune system, which may open new venues for CHB therapies.